Influence of pH on Pb accumulation in the blue mussel, Mytilus edulis. (July 2020) - Belivermiş, Murat; Besson, Marc; Swarzenski, Peter; Oberhaensli, François; Taylor, Angus; Metian, Marc
Abstract: Changes in seawater pH can alter the chemical speciation of waterborne chemical elements, affecting their bioavailability and, consequently, their bioaccumulation in marine organisms. Here, controlled environmental conditions and a 210 Pb radiotracer were used to assess the effect of five distinct pH conditions (pHT ranging from 7.16 to 7.94) on the short-term (9 days) accumulation of Pb in the blue mussel, Mytilus edulis . After 9 days of exposure, higher levels of Pb were observed in the soft tissues of mussels maintained in the lower pH conditions, while Pb levels accumulated by mussel shells showed no difference across pH conditions. These results suggest that pH decreases such as those predicted by ocean acidification scenarios could enhance Pb contamination in marine organisms, with potential subsequent contamination and effect risks for human consumers. Highlights: Acidification increases lead bioconcentration in mussel soft tissues. This process is rapid and is observed after only 9 days of exposure to lead. Acidification increases the risk of lead contamination for mussel consumers.